Valentino’s syndrome: the simulation of an appendicitis - González Chávez, Alberto Manuel; García Vázquez, Alain Arturo; Gómez López, José Manuel; Pavón, Nicolás Leyva; Lemus Gómez, José Luis; Álvarez Hernández, Diego Abelardo; Durón, Mauricio Valdez (International Surgery Journal, 2017)
Acute abdominal pain is still the domain of the surgeon. Among the many differential diagnosis that should be considered, acute appendicitis must be one of the main options for the clinician. Even though we have excellent diagnostic tools nowadays, accomplishing an accurate diagnosis is not that easy. We all know that is better to perform surgery on a normal appendix than not operating an appendix that will result in complications; we also know that the diagnostic challenge will be higher in a female patient. But, what if right lower quadrant pain is produced by a pathology that doesn’t involve that anatomical region? We present two cases that clearly explain this situation.